1993
DOI: 10.1128/mcb.13.7.4331-4341.1993
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the SKI Antiviral System of Saccharomyces cerevisiae Acts by Blocking Expression of Viral mRNA

Abstract: The SKI2 gene is part of a host system that represses the copy number of the L-A double-stranded RNA (dsRNA) virus and its satellites M and X dsRNA, of the L-BC dsRNA virus, and of the single-stranded replicon 20S RNA. We show that SKI2 encodes a 145-kDa protein with motifs characteristic of helicases and nucleolar proteins and is essential only in cells carrying M dsRNA. Unexpectedly, Ski2p does not repress M1 dsRNA copy number when M1 is supported by aN L-A cDNA clone; nonetheless, it did lower the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Subsequent studies demonstrated that, in addition to the exosome, the products of SKI2 , SKI3 and SKI8 genes are required for the 3′‐mRNA degradation (Jacobs Anderson and Parker, 1998). Ski2p, Ski3p and Ski8p are a putative RNA helicase, a tetratricopeptide‐repeat protein and a protein containing WD motif, respectively (Rhee et al ., 1989; Matsumoto et al ., 1993; Widner and Wickner, 1993). The three Ski proteins form a stable complex, and the complex is localized in the cytoplasm (Brown et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies demonstrated that, in addition to the exosome, the products of SKI2 , SKI3 and SKI8 genes are required for the 3′‐mRNA degradation (Jacobs Anderson and Parker, 1998). Ski2p, Ski3p and Ski8p are a putative RNA helicase, a tetratricopeptide‐repeat protein and a protein containing WD motif, respectively (Rhee et al ., 1989; Matsumoto et al ., 1993; Widner and Wickner, 1993). The three Ski proteins form a stable complex, and the complex is localized in the cytoplasm (Brown et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, we would like to investigate what advantages are provided by the cap and poly(A) structures on the AaV1 dsRNA genomic segments. The SKI genes are involved in 5'-3' and 3'-5' mRNA degradation pathways (Toh-E et al, 1978;Widner and Wickner, 1993;. Therefore, we will utilize SKI-deficient mutants or SKI-overexpressing strains of Saccharomyces cerevisiae, since this might provide valuable insights into the roles of the cap and poly(A) structures in RNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous TFs are involved in this complex regulatory network. The virus might act towards the activation of genes required for its replication (e.g., MAK3, MAK10, and MAK31 [17,21,22]), whereas the host may induce the expression of genes involved in virus suppression (e.g., XRN1/SKI1, SKI2, SKI3, SKI7, SKI8, NUC1, and POR1/2 [28,33,44,45]) to control virus propagation and vice versa. Similarly, the virus may contribute to the repression of the transcription of genes conflicting with its functioning; similarly, the host might inhibit the expression of genes that aid the virus.…”
Section: Interconnection Between Transcription Factors and L-a Dsrna ...mentioning
confidence: 99%
“…L-A virus propagation is controlled or inhibited by systems found in yeast cells. Nascent L-A mRNA has neither cap nor polyA tails [32]; thus, its 5 -end is prone to degradation by exonuclease Xrn1/Ski1, whereas cytoplasmic exosome degrades mRNA, which lacks a polyA tail in the 3 -end [12,33]. Xrn1 is involved in the regulation of various cellular processes, including meiosis [34], filamentous growth [35], RNA turnover [36], control of telomere length [37], respiration [38], and autophagy [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation